2011
DOI: 10.1186/1471-2474-12-8
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and validity of the shoulder pain and disability index in a population-based study of people with shoulder symptoms

Abstract: BackgroundThe Shoulder Pain and Disability Index (SPADI) is a self-administered questionnaire that aims to measure pain and disability associated with shoulder disease. The aim of the present study was to investigate the construct validity and factor structure of the SPADI in a population-based study of patients with self-reported chronic shoulder symptoms.MethodsThe North West Adelaide Health Study is a representative longitudinal cohort study of people aged 18 years and over. The original sample was randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 18 publications
8
50
0
Order By: Relevance
“…Correlation coefficients found in other studies for convergent validity varied between moderate and high [4,[24][25][26]. Few studies evaluated divergent validity of the SPADI and none used the EQ-5D-3L [25,26].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Correlation coefficients found in other studies for convergent validity varied between moderate and high [4,[24][25][26]. Few studies evaluated divergent validity of the SPADI and none used the EQ-5D-3L [25,26].…”
Section: Discussionmentioning
confidence: 89%
“…Few studies evaluated divergent validity of the SPADI and none used the EQ-5D-3L [25,26]. Only one study reported a factor structure as originally described by Roach [26], the majority of studies could not confirm this loading pattern or reported a one-factor structure [6,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al 25 tested the internal consistency in 588 patients with shoulder disorders, with a [ research report ]…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review revealed that the intraclass correlation coefficient (ICC) was greater than 0.89 (33). Internal consistency was high, with Cronbach's α typically exceeding 0.90 (33,34). An 8-point change in SPADI was reported as the MCID among patients with shoulder pain (35).…”
Section: Outcome Measuresmentioning
confidence: 99%